Legalitas dan Perlindungan Hukum terhadap Investasi Kripto Syariah: Analisis Maqashid Syariah dan Peraturan di Indonesia - Syahril Fadhlurrahman (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2025)
The development of digital technology has given birth to various new investment instruments, including crypto assets. The emergence of sharia crypto as an alternative halal investment has raised debates from the aspect of sharia economic law, both in terms of fiqh and positive regulations in Indonesia. This article aims to examine the validity and legal protection of sharia crypto investments based on the principles of maqashid sharia and its synchronization with national regulations such as the Bappebti Regulation and the DSN-MUI Fatwa. The method used is juridical-normative with a conceptual and comparative legal approach. This study found that most crypto does not meet the criteria as mal mutaqawwam (valuable assets in sharia), mainly due to the high elements of gharar (uncertainty) and speculation. However, several crypto projects based on real assets and transparent smart contracts are starting to offer potential sharia investment models. On the other hand, Indonesian government regulations through Bappebti have begun to classify crypto as a tradable commodity, but have not touched on the aspect of protection of sharia principles. Therefore, it is important to have a legal umbrella that strictly regulates sharia crypto, both in terms of contracts, investor protection, and transaction mechanisms. With the maqashid sharia approach, protection of assets (hifz al-mal) and justice in muamalah become important bases for the legality of crypto investment that is in line with Islamic principles and national law.